Performance of Trees in the Semi-arid Sub-tropics for Production of Chickpea in Rain-fed Conditions - Gill, A. S. (Indian Forester, 2009)
Studies were initiated with four important tree species (Albizia lebbek, Azadirachta indica, Dalbergia sissoo and Acacia nilotica) by raising chickpea in their interspaces in the semi-arid sub-tropics at the Indian Grassland and Fodder Research Institute, Jhansi under rain-fed conditions (1998-2005). On the basis of various growth characters as recorded among the trees, on an average best performance was found in Dalbergia sissoo closely followed by Acacia nilotica and Albizia lebbek and poorest growth was noticed in Azadirachta indica. Same trend in the production of chickpea from the inter paces of the trees was recorded. On an average., highest grain and straw yield was achieved from the interspaces of Dalbergia with a relative grain yield of 96.0% and relative straw yield of 91.5%. There was a marginal loss of grain yield to the extent of 4% on an average, which was compensated from the production of the trees.